3D spatial operations – topology vs. geometry - Chen, T. K. (2008)
Geo-DBMS becomes very important medium for GIS as it can handle and manage (e.g. retrieve and update) large volume of spatial data. Providing 3D spatial database with appropriate operation tools such as 3D spatial operations would be very useful for next generation of GIS software (i.e. 3D GIS) since the software would highly depend on the Geo-DBMS in both modeling and analysis. One of the desired components in such future software or system is geometric modeling capability that works with 3D spatial operations. The literature reveals 3D spatial database would be greatly enhanced if analytical operations on the spatial data could be manipulated in real 3D domain. Fundamentally, it can be considered that the aspect of 3D spatial operations within GIS software are still not much been addressed and solved as expected (i.e. up to the level where an operational 3D system could be realized). The main problem from this aspect is the unavailability of 3D spatial data type within geo-DBMS environment. It is the aim of this paper to describe 3D spatial operations for geometrical and topological data types within geo-DBMS environment. In the experiment, we utilize an existing geo-DBMS, PostgreSQL, later known as PostGIS, which complied with the standard specifications from Open Geospatial Consortium (OGC), e.g. abstract and geometry specification. The second factor why we utilise the PostGIS is because its an open source based technology and suitable for academic and research purposes. In this paper, we discuss a suitable way of developing a new 3D data type, polyhedron, for both geometrical and topological data types and spatial operations using C language.